Solitary Magnetic Structures at Quasi‐Parallel Collisionless Shocks: Formation. Issue 1 (12th January 2021) - Chen, Li‐Jen; Wang, Shan; Ng, Jonathan; Bessho, Naoki; Tang, Jian‐Ming; Fung, Shing F.; Le, Guan; Gershman, Daniel; Giles, Barbara; Russell, Christopher T.; Torbert, Roy; Burch, James
Abstract: Solitary magnetic structures known as SLAMS (short large‐amplitude magnetic structures) have been considered as essential elements of collisionless shocks with quasi‐parallel geometries. Yet the physics underlying their formation remains an open question. In this paper, we use measurements from the magnetospheric multiscale mission combined with fully kinetic simulations to study the formation of SLAMS. We find that gyro‐resonance between solar wind ions and right‐hand circularly polarized electromagnetic waves results in magnetic field amplification. Gyro‐trapping by the growing magnetic field buildup the plasma density that further enhances the current and field. The solitary nature of SLAMS stems from a beat‐like magnetic field envelope where the maximum sets the initial location for nonlinear growth. Our results present a conceptual advance on SLAMS, and may shed new light on the open question of magnetic field amplification at astrophysical shocks. Plain Language Summary: We integrate MMS measurements and fully kinetic simulations to investigate the nonlinear processes underlying ultra‐low‐frequency wave growth and evolution into solitary magnetic structures known as SLAMS. The understanding gained here presents a conceptual advance on the formation of SLAMS at planetary bow shocks, and may serve as new insight into how magnetic fields in the interstellar medium are amplified to create an environment for cosmic ray production at astrophysical shocks. Key Points: Gyro‐resonance between solar wind ions and right‐hand circularly polarized electromagnetic waves results in magnetic field amplification Gyro‐trapping by the growing magnetic field buildup the plasma density that further enhances the field growth The solitary nature of SLAMS stems from the magnetic field envelope where the maximum sets the initial locations for nonlinear growth